The Forecast Method of Isolation Resource for Creating the Integral Characteristics of Overvoltages - Karaliūtė, U.; Miliūnė, R.; Navickas, A. S. (Elektronika ir Elektrotechnika, 2010)
For the forecast and the evaluation of the resource expenditure of electric equipment insulation it is necessary to know the integral characteristics of overvoltages. The evaluation method of Insulation resource is used in the theoretical and practical integral characteristics. The theoretical integral characteristics are derived from described characteristics of the manufacturer's recommended and standards. The register of the integral characteristics are made the practical integral characteristics by measured overvoltages. The register of the integral characteristics is connected to the voltage transformer buses allows the analysis of effect overvoltages and the evaluation of the resource expenditure of the electric equipment insulation. The overvoltages influencing the electrical equipment insulation can be estimated according to the registered integral characteristics.